Correction: Thiadiazole containing N- and S-rich highly ordered periodic mesoporous organosilica for efficient removal of Hg(II) from polluted water. Issue 90 (1st November 2021) - Das, Surajit; Chatterjee, Sauvik; Mondal, Saptarsi; Modak, Arindam; Chandra, Bijan Krishna; Das, Suparna; Nessim, Gilbert Daniel; Majee, Adinath; Bhaumik, Asim
Abstract : Correction for 'Thiadiazole containing N- and S-rich highly ordered periodic mesoporous organosilica for efficient removal of Hg(II) from polluted water' by Asim Baumik et al., Chem. Commun., 2020, 56, 3963–3966, DOI ; 10.1039/D0CC00407C .